2022
DOI: 10.2478/aoas-2021-0082
|View full text |Cite
|
Sign up to set email alerts
|

The importance of nutrition in alleviating high stocking density stress in poultry - A Review

Abstract: In recent decades, the number of birds reared per unit area has dramatically spiked to increase profitability in egg and meat production. However, nowadays, the increase in sensitivity to animal welfare and consumer demands brings along with it a raised interest in stocking density. Stocking density is defined either as the number of animals or body weight per unit area or as the area per animal. High stocking density, which is a stress factor, can be defined as an increase in the number of animals per unit ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 91 publications
1
2
0
Order By: Relevance
“…According to the results of research, it is shown that high crowding of hens to 24.0 birds m -2 leads to an increase in heterophils by 1.8%, to 25.3 birds m -2 -by 3.1%; to 26.7 birds m -2 causes an increase of their content by 13.5%. The obtained data on the increase in the content of heterophils coincide with the results obtained in similar experiments with overcrowding of laying hens, as well as in broiler chickens during stress, and stress from starvation, heat, and immobilization stress (Kang et al, 2018;Li et al, 2019;Nwaigwe et al, 2020;Gul et al, 2021).…”
Section: Resultssupporting
confidence: 86%
“…According to the results of research, it is shown that high crowding of hens to 24.0 birds m -2 leads to an increase in heterophils by 1.8%, to 25.3 birds m -2 -by 3.1%; to 26.7 birds m -2 causes an increase of their content by 13.5%. The obtained data on the increase in the content of heterophils coincide with the results obtained in similar experiments with overcrowding of laying hens, as well as in broiler chickens during stress, and stress from starvation, heat, and immobilization stress (Kang et al, 2018;Li et al, 2019;Nwaigwe et al, 2020;Gul et al, 2021).…”
Section: Resultssupporting
confidence: 86%
“…Similarly, Ahmed et al (2022) demonstrated that as cage SD increased (from 252.20 to 106.73 cm 2 / bird) for Japanese quail hens their egg production rate, total egg mass and FCR were adversely affected. Generally, it has been reviewed that stress induced by increasing SD for different classes of poultry negatively affects their performance, physiological indices and the quality of their products (Gül et al, 2022). It seems that the optimal rates of SD of poultry depend on some factors such as season, species, gender, type of production (broiler chicks vs. laying hens), housing system (battery cages vs. floor pens) and housing conditions (open houses vs. environmentally controlled houses).…”
Section: Resultsmentioning
confidence: 99%
“…Several managerial and nutritional strategies can be adopted to minimize the negative effects of high SD on the welfare and performance of poultry. Some of these strategies have been reported including dietary supplementation with vitamin E (Selvam et al, 2017), yeast extract (Reda et al, 2021), organic acids (Dai et al, 2022), probiotics, prebiotics, synbiotics, plant-derived products, vitamins, and fatty acids (Sugiharto, 2022) and increasing the ND of the diet (DePersio et al, 2015;Khatibi et al, 2021;Gül et al, 2022). Therefore, the present study was designed to evaluate the response of laying Japanese quail stocked at three cage densities to feeding highnutrient-density diets.…”
Section: Introductionmentioning
confidence: 99%